Narrow Artificial Intelligence Weapons Systems and their Impact on the Balance of Power - Tsitsiringos, Alexandra T. (Tufts University. Tisch Library., 2020)
Yale Review of International Studies Publication. The paper asks the question: How might the diffusion of military-driven narrow AI weapons platforms shift the balance of power between states that invest in such platforms and states that have not invested in them? The paper explores whether public-private cooperation is necessary to develop AI weapons platforms and whether countries that develop such platforms early will have substantial “first-mover” advantages. It also examines how the broad adoption of AI might lead to the emergence of a new global leader or an AI arms race.